Discourse on the Death Penalty: A Study of Public Perceptions in Indonesia - Djatmika, Prija; Istiqomah, Milda; Kurniawan, Heru (Yustisia, 2024)
The current debate over the death penalty between the retentionist and abolitionist groups is addressed in Decision Number 2-3/PUU-V/2007 of Indonesia, establishing a middle ground. Originally, the death penalty was a primary punishment in the Old Criminal Code but is now reserved as a last resort in the New Criminal Code. Therefore, this research aimed to analyze public perspectives on the death penalty in Indonesia using mixed methods with data collection through questionnaires. The research showed continued contention over the regulation of the death penalty. A large percentage of participants expressed support for maintaining the death punishment, indicating a retentionist viewpoint. Nevertheless, quite a few of the participants supported the abolition. Indonesia should reconsider the regulation of the death penalty for certain offences as Malaysia, even though the punishment in the New Criminal Code was classified as an alternative sanction because the death penalty was an irreversible punishment.